FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK - Lely Ika Cahyani, 09.05.52.0152; Astuti, Sih Darmi (Students Journal of Accounting and Banking, 2013)
The study was conducted to determine the influence knowledge of tax regulations, tax regulations understanding, effectiveness perception of tax system, service quality, modernization of tax administration system, and willingness to pay tax towards taxpayer compliance. This descriptive statistical research, using individual taxpayers registered in the Small Tax Office (STO) Semarang Gayamsari as the research object. Data obtained from the questionnaire which is primary data and was given to 100 respondents using convenience sampling method. The results were analyzed using SPSS software version 16, concluded that knowledge of tax regulations affects tax regulations understanding positively and significant. Then tax regulations understanding affects willingness to pay tax positively and significant. The last one is effectiveness perception of tax system and service quality affects tax compliance positively, and significant except willingness to pay tax which affects tax compliance negatively and significant.Keywords: knowledge of tax regulations, effectiveness perception of tax system, service quality, modernization of tax administration system, taxpayer compliance.